Patients Satisfaction with Dental Service, School of Dentistry, University of Costa Rica = Satisfacción de los usuarios del Servicio de Odontología, Universidad de Costa Rica - Gutiérrez Marín, Natalia 1975-
The objective of this research was to use the Dental Satisfaction Questionnaire to determine the level of patient's satisfaction who come to the School of Dentistry of the University of Costa Rica. The research was conducted with the entire population of patients who received dental care in the Undergraduate Student Clinics of the School of Dentistry between April and September 2021. A digital survey was generated with the questions of the DSQ and sociodemographic variables, which was sent by email. Descriptive statistics were performed to establish the absolute and relative frequency, as well as measures of central tendency and variability, according to the nature of the variables. The Kolmogorov-Smirnov test was used in the conformity assessment of the data for the normal distribution. The relationships between the scores obtained from the Dental Satisfaction Questionnaire and the sociodemographic variables were analyzed using the Mann-Whitney U Test and the Kruskal-Wallis Test. A response rate of 36% was obtained. 98.5% of the subjects were satisfied with the services received. There was a statistically significant difference between the frequency of visits and the dental satisfaction scale (p=0.001). The scoring by type of clinic with regards to access, pain management, cost and availability were statistically significant (p=0.001, p=0.014, p=0.001, p=0.001, respectively). The differences in the relationship between the age groups and access was significant (p=0.014); in addition to that between education level and cost (p=0.001). A large majority of patients who come to the services of the School of Dentistry UCR are satisfied with the service received.